PROTOTYPE OF AUTOMATIC DISINFECTANT TOOL BASED ON INTERNET OF THINGS (IOT) IMPROVES HEALTHY LIVING HABITS - Binazun, Inayah; Adzin Murdiantoro, Randi; Nasrulloh; Munawar, Aris; Fachruroji (Journal of Electronic and Electrical Power Applications, 2024)
Covid is currently starting to subside, one of which is with the handling, recommendation for vaccines from dose 1 dose 2 and booster vaccines. Handling and recommendation for vaccines is one form of government policy and is one of the government's responsibility efforts to the community. The use of disinfectants can be one solution for the community to start living a healthy and clean life, but many people are reluctant to bring disinfectants to public places. The existence of a prototype of an automatic disinfectant tool can provide a solution for people who are reluctant to bring disinfectants out of the house, even every community house can make an automatic disinfectant tool for indoor use. Based on the results and discussions above, it can be concluded that the design of the prototype of an automatic disinfectant sprayer with a proximity sensor based on the internet of things (IOT) to support healthy living habits after the pandemic has been successfully carried out. While the results of the efficiency of the proximity sensor detection time against objects were 86.3% with a proximity sensor error value of 2.1%. The prototype of an automatic disinfectant sprayer with a proximity sensor based on the internet of things (IOT) has successfully sent the results of the prototype disinfectant usage counter to the telegram. Although there are still many shortcomings in this study in building a prototype of an automatic disinfectant sprayer with a proximity sensor based on the internet of things (IOT), the overall system that was built can run well..